Mapping the Potential of Faculty of Teacher Training Education Lecturers in the Field of Study Program Development Innovation, Work Mindset, and Competitive Entrepreneurial Attitudes in the Digital Area - Wahidin; Nana; Mufti Ali; Agus Sumantri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This study aims to map the innovation potential of Lecturers. Aspects of the study include competence, demography and socio-culture with work mindset variables, entrepreneurial attitudes, and Study Program development innovations. Next studied the relationship between these variables. Data collection was carried out by random sampling via electronics to the lecturer population at Faculty of Teacher Training Education. The results of the returned and valid questionnaire were 33 samples. Descriptive data processing of each component is studied one by one and analyzed followed by a simple correlation test, using SPSS software. The results of the study show that demographically and socio-culturally the lecturers have positive potential with high confidence from the dimensions of the work mindset and entrepreneurial attitude at a sufficient stage to carry out innovations in the development of the Study Program. Meanwhile, between one variable and another, there is no correlation with the innovation of the Study Program development. This research paved the way that faculty collaborative programs related to innovation in the development of Study Program with stakeholders to increase the social cohesiveness and entrepreneurial attitudes of lecturers. It is necessary to improve the quality of innovation collaboration between lecturers and colleagues to face the demands of competitiveness in the digital era. Further studies are needed on the innovation model of Study Program development for the synergy of work mindsets, entrepreneurial attitudes with innovation in the development of Study Program for all faculties in the university.